Stability analysis of different control modes of grid-connected converters under different grid conditions - Xu, Zhi; Qin, Yanhui; Li, Zian; Jiao, Chunlei; Zhai, Baoyu; Chang, Xiqiang (Frontiers in Energy Research, 2023)
With the sustained popularity of renewable energy generation, high penetration of variable energies, e.g., wind and solar, is reshaping the form of power systems and weakening the strength of the grid. The stability mechanism of the grid-connected converter in a weak power network, however, has yet to be evaluated. This paper establishes impedance and transient models for Grid-Following (GFL) as well as Grid-Forming (GFM) converters through the impedance analysis method and equal area criterion analysis method. The stability of these two control methods is then comprehensively studied under small and large interference with different grid conditions. The analytical results show that the GFM control is more stable against small disturbances in a weak network. In contrast, it is prone to a significant disturbance stability problem in the strong grid due to the large grid impedance. The GFL control is more suitable for a vigorous power grid, whereas introducing oscillation in a weak power grid due to its negative damping. Simulation experiments have verified the accuracy of the analytical results.